Validation of the scale of assessment of self‐care behaviours for arteriovenous fistula in patients ongoing haemodialysis in Turkey. Issue 4 (2nd November 2020) - İkiz, Saime Nuray and Usta, Yasemin Yıldırım and Sousa, Clemente Neves and Teles, Paulo and Dias, Vanessa Filipa Ferreira and Magalhães, Anna Luiza Pereira and de Sá Basílio Lins, Silvia Maria and Ribeiro, Olga Maria Pimenta Lopes
Abstract: Background: Several guidelines recommend that patients with chronic kidney disease treated by haemodialysis (HD) take care of their own arteriovenous fistula (AVF). The dialysis nurse plays an important role in the development of such self‐care behaviours. A very small number of instruments are available to assess self‐care behaviours with AVF in Turkey. Objective: Cultural adaptation and psychometric testing of the Turkish version of the scale of assessment of self‐care behaviours with arteriovenous fistula in haemodialysis (ASBHD‐AVF) patients. Design: Cross‐sectional validation study. Participants and Measurements: This study was conducted involving 160 patients in the Bolu region in Turkey. The guidelines provided by Sousa and Rojjanasrirat were taken into account in the scale translation, adaptation and validation process. Validity was analysed through content validity and construct validity. The latter was measured through principal component analysis with varimax rotation, considering only factor loadings of 0.30 or larger. Reliability analysis was based on internal consistency measured by Cronbach's α. Results: A two‐factor structure was extracted explaining 59.01% of the total variance. Cronbach's α was 0.91, 0.85 and 0.84 for the overall scale, the self‐care in prevention of complications subscale and the self‐care in management of signs and symptoms subscale, respectively. Conclusions: The Turkish version of the scale of ASBHD‐AVF patients is a reliable and valid instrument and can therefore be used.